Ghana : Three-Year Arrangement Under the Extended Credit Facility-Request for Modification of Performance Criterion-Staff Report. (IMF Staff Country Reports; Country Report, 2011)
The report gives the details of the Ghanaian authorities' request for modification of the performance criterion under the Extended Credit Facility (ECF)-supported program. The proposed loan involves borrowing at nonconcessional terms. The authorities' request is with the intention to consider modification of the limit on external borrowing at nonconcessional terms in the context of the combined first and second reviews to accommodate new high-return projects, in line with the new IMF policy on debt limits.